The nature of sleep examined via the science of sleep - Hussain MV (Dove Medical Press, 2011)
Mohammad Viqar Hussain, Steven Andrew SheaDivision of Sleep Medicine, Harvard Medical School and Brigham and Women’s Hospital, Boston, MA, USAThe phenomenon of sleep is so curious from almost every vantage point: historical, cultural, scientific, and medical. The Nature and Science of Sleep is a new journal that aims to publish original research and reviews that will help unravel the mysteries of sleep, and improve our understanding of sleep disorders in humans. The success of a new journal can be unpredictable. Ideally there would be a high threshold for publication of only important and robust findings or very well considered reviews, yet the best scientists and authors may be reluctant to put their best work in a new journal because there is a perceived risk that the new journal will not become popular. However, publishing in the Nature and Science of Sleep provides authors with numerous advantages. First, we are committed to making this journal a success. As an example of this, the Nature and Science of Sleep has one of the fastest turnaround times for peer review and editor's approval among medical journals, with an average review plus editorial decision in less than 2 weeks and online publication soon after. Second, we provide open access publishing so that all papers are freely available to anyone in the world directly from the website. Third, our editorial board comprises many of the world's distinguished scientists within the field of sleep research and sleep medicine, which provides a great foundation for this journal. Fourth, we anticipate that in the near future all publications within this journal will be available through PubMed and other searchable databases.